The power of engagement: understanding active social media engagement and the impact on sales in the hospitality industry / Tasha Peter - Peter, Tasha (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA Sarawak, 2022)
The goal of this study is to learn about the most essential characteristics of active social media engagement among followers of a food and beverage sales company, as well as the impact of social media engagement rate on new product sales. The research shows that highly engaged social media posts improve company success by increasing sales. Additionally, the study uses text mining algorithms to find the most successful usage of social media platforms, providing a recipe for success. The text mining techniques indicate the optimal date/time, type of posting, hashtag to utilize, and social media platform to use for maximum engagement.